(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Shifonemas or shifonyms - medicinal plant names play a crucial place in modern linguistics, as they are essential for communication among botanists, scientists, and individuals who are interested in plant life. The study of shifonemas is an important area of research for linguists and botanists, as it provides insights into the cultural and linguistic aspects of plant life. In this article, we will explore the place of shifonemas in modern linguistics and their significance in the field